In Blockchain We Trust: Does Blockchain Itself Generate Trust? - Shin, Donghee; Bianco, William T. (Social Science Quarterly (Wiley-Blackwell), 2020)
Objectives: This study considers the affordance of users' perceived technological property of blockchains and investigates how users discover the possible actions that can be performed within blockchain media. With a focus on the role of trust, it analyzes how motivational affordances in blockchain media influence user experience Methods: Qualitative methods are used to obtain the depth of understanding and elicit the perspective of blockchain media. We then conduct a survey to analyze the affordance of trust in the acceptance of blockchain media Results: Our confirmed model indicates a heuristic dimension of trust regarding underlying ties to affective and technological affordances. These findings imply that cognitive heuristics affect users' decision making about privacy and security on blockchain media. These heuristics lead users to engage in uncertain and even risky transactions in blockchain media. Conclusions: Despite the exponential growth in blockchain development, there has been little attention paid on how technological innovations of blockchains can produce value in the media sector. Our findings provide a lens to understand the blockchain's usability problems by pairing heuristics to blockchain design and user experience principles.